How quickly she disappears - Fleischmann, Raymond (Berkley, 2020)
"The Dry meets The Silence of the Lambs in this intoxicating tale of literary suspense, set in the relentless Alaskan landscape, about madness and obsession, loneliness and grief, and the ferocious bonds of family.... My proposition is very simple: I am going to ask you for three gifts, and for each gift you deliver, I will take you one step closer to Jacqueline. It's been twenty years since Elisabeth watched her twin sister, Jacqueline, disappear without a trace. Now thirty-year-old Elisabeth is living far from home in a small Alaskan town. She's in a loveless marriage and has a precocious young daughter she loves more than anything but who reminds her too much of her long-missing sister. Elisabeth's loneliness--and guilt--grows more unbearable each day. But through it all, she clings to the impossible belief that her sister is still alive and that they'll be reunited. But then Alfred, a dangerous stranger with a plan of his own, arrives in town and commits an inexplicable act of violence. And he offers a startling revelation: He knows exactly what happened to Elisabeth's sister, but he'll reveal this truth only if Elisabeth fulfills three requests. Increasingly isolated from her neighbors and imprisoned by the bitter cold and her own obsession, Elisabeth can almost hear her sister's voice saying, Come and get me. And so she will, even if it means putting herself--and her family--in danger"--